Tactical analysis of individual and team behaviour in professional Australian Football: Original investigation. Issue 2 (3rd April 2022) - Sheehan, William B.; Tribolet, Rhys; Watsford, Mark L.; Novak, Andrew R.; Rennie, Michael; Fransen, Job
ABSTRACT: Introduction: This study sought to reduce the dimensionality of commonly reported spatiotemporal characteristics obtained from Australian Football games to facilitate their practical use and interpretability. Methods: A retrospective longitudinal design was utilised with team and individual spatiotemporal variables, measured via global navigation satellite system devices, collected during official Australian Football League matched over three seasons. Two separate principal component analyses were conducted at the team and individual level to reduce correlated spatiotemporal characteristics into a smaller set of uncorrelated components. Results: At the team level, eighteen variables were reduced to five components pertaining to dispersive coordination, lateral predictability and spacing, multidirectional synchrony, longitudinal predictability and longitudinal behaviour whilst maintaining 69% of variance in the original dataset. At the individual level, fifteen variables were reduced to four components pertaining to multidirectional and spacing synchrony, unpredictability, player movement and player positioning whilst maintaining 64% of variance. Conclusion: This study is the first to provide a simplified, novel method for analysing spatiotemporal behaviour in an Australian Football context with both the team- and individual- derived metrics revealing useful information for coaches and practitioners. Components may provide insight into behaviours that emerge and persist throughout a game and allow coaches to distinguish between different playing/behavioural styles